Economic Valuation of Tree Species Diversity at Ayer Hitam Forest, Selangor, Peninsular Malaysia - Ibrahim, Faridah Hanum; P., Pius; Abd. Ghani, Awang Noor (Universiti Putra Malaysia Press, 1999)
From a study conducted on a 1-ha plot at the Ayer Hitam Forest, Selangor, a total of 177 species in 92 genera and 44 families were enumerated. The stand density was 909 trees per ha. Stumpage values for below cutting limit were RM 8707.52 and RM 17514.12 per hafor upper cutting limit. The total stumpage value was RM 26221.64 per ha. The family Sapotaceae contributed the highest stumpage value accounting for half the total stumpage value obtained. The commercial groups nyatoh and kedondong accounted for 52% and 25% of the total stumpage value, respectively.